Importance of Employee Motivation and Commitment on Innovative Behaviors - Amir Mohammed Haya; Alpaslan Toker (Eurasian Journal of Management & Social Sciences, 2022)
Job (organizational) commitment is defined as the psychological attachment of an employee to their organization; a responsibility to stay in their current position. Innovative behavior is an effective factor for organizations to be able to survive with environmental changes and be sustainable. Innovative behavior helps organizations to be competitive and sustainable in the market. Further, employee motivation is the level of energy, commitment, and creativity that a company’s workers bring to their jobs. In this respect, current paper proposed to test the relationship among employee motivation, commitment, and innovative behaviors. To reach that, we have organized a survey questionnaire and visited various companies in Sulaymaniyah city in Kurdistan Region. As a result, 132 data have been collected. Accordingly, it has been observed that employee commitment and motivation positively related to employees’ innovative behaviors in the region. It is recommended that residential managers should provide commitment and motivation-oriented trainings to improve employee in the company.